Dental Students' Knowledge and Attitudes towards Antibiotic Prescribing Guidelines in Riyadh, Saudi Arabia - Abdulrahman AboAlSamh; Abdulmalik Alhussain; Nawaf Alanazi; Rakan Alahmari; Naila Shaheen; Abdallah Adlan (MDPI AG, 2018)
Background: The use of antibiotics prophylactically and therapeutically in dentistry has become common practice. Inappropriate prescription may lead to adverse side effects and bacterial resistance. During clinical training, dental students in Saudi Arabia are authorized to prescribe antibiotics. Aim: To evaluate dental students’ knowledge and attitudes regarding antibiotic prescription in Riyadh, Saudi Arabia. Methods: A cross-sectional study based on a validated questionnaire consisting of 34 questions focusing on antibiotic indications in dentistry, antibiotic regimens, and knowledge regarding resistance was distributed amongst dental students in five leading dental colleges in Riyadh. Results: A large proportion of students (71.7%) were familiar with the concept of antibiotic resistance. When comparing junior and senior dental students’ knowledge with regards to indications of antibiotic use in commonly encountered conditions, it was found that there was no significant difference in antibiotic prescription frequency between these groups. Most dental students choose to prescribe amoxicillin as their first-choice of antibiotic (88.4%), and most also chose to use it for a duration of 3–5 days (69.2%). Conclusions: This study concludes that dental students may prescribe antibiotics inappropriately to manage various conditions when not indicated. This may indicate a defect in education of students with regards to current antibiotic guidelines.